OCCURRENCE OF A POSSIBLE DWARFISM IN BUFFALOES: A CASE REPORT - Schettini, Gustavo Pimenta; Tonizza de Carvalho, Nelcio Antonio; Tonhati, Humberto [UNESP]; Costa, Raphael Bermal; Ferreira de Camargo, Gregorio Miguel (Int Buffalo Information Ctr, 2020)
The detection and control of congenital diseases are important to maintain productive and reproductive indexes. The dwarfism is characterized by fetal incomplete or malformation. The present report states a possible dwarfism in buffaloes. The calf presented a low birth weight and a slow weight gain. The animal had also an asymmetric skull and deformed members, especially the hind legs. The calf died at eight months of age. Investigations of reproductive historical of parents were done and hypotheses to explain the event were presented.
Keywords: Bubalus bubalis; buffaloes; low weight; deformed calf; mutation